Prawne i koncepcyjne aspekty opracowania systemu monitoringu zagospodarowania przestrzennego w Polsce - Wrochna, A.; Kozubek, E. (Видавництво Національного університету «Львівська політехніка», 2009)
Статья посвящена вопросам связанным с периодическими и концептуальными аспектами разработки системы ониторинга пространственного планирования в Польше . Представлены инициативы и методические предложения направление на разработку концепции системы мониторинга которая даст возможность учитывать как национальный так и региональный уровень. In the paper the problem of the development of a system for spatial planning monitoring is undertaken. The legal possibilities and restrictions connected with the designing and creation of such system are indicated. A review of the activities on this area is also presented together with the proposal of methodological solutions necessary for developing a concept of the monitoring system which would enable to generate spatial-based information at national and regional scale.